Monte Carlo study of a new experiment at RHIC measuring the nuclear effect for cosmic ray observations. (14th September 2017) - Suzuki, T.; Itow, Y.; Kasahara, K.; Sako, T.; Torii, S.
Abstract: We have studied the potential performance of an experiment designed to measure neutral particles emitted in the forward region ( η>6 ) of proton-nitrogen (p-N) inelastic collisions at √ s NN =200 GeV. Such measurements will provide for the first time direct information about interactions between proton cosmic rays and the atmosphere at collider energies and will aid in the understanding of the nuclear effect of light-ions in the forward region which is expected to be dominated by the shadowing effect due to rescattering inside nuclear matter; this in turn will allow for the development of better air shower models. We first studied differences among the nuclear effects produced by the interaction models QGSJETII-03, DPMJET 3.04, and EPOS 1.99. We quantified the nuclear effects by calculationg the ratio of energy spectra of p-N collisions and proton-proton (p-p) collisions, which revealed a difference at the 30% level in the forward pion and neutron spectra. In order to assess the expected performance of an experiment designed to measure this difference, a full Monte Carlo calculation was conducted assuming the use of the Relativistic Heavy Ion Collider forward (RHICf) detector at Brookhaven National Laboratory installed at 1, 800 cm from the interaction point. We have comfirmed that the detector would be able to identify and measure photons of energies below 100 GeV with position and energy resolutions better than 0.4 mm and 16%, respectively. One can discriminate the nuclear effect incorporated into various interaction models used in air shower simulations by measuring the photon spectrum in two different pseudorapidity ranges: η>10.5 and 8.8<η<10.2 .